A magyarországi egyetemtörténet-írás eredményei és feladatai - Szögi, László (Per Aspera ad Astra, 2017)
In the following paper we display the development of writings about universities history in the last 25 years. It is important to underline that we use the name of Hungary as a historical definition. In this case it means the whole territory of the Carpathian Basin, because the current boarders were created in 1920. Since the Hungarian universities were founded late the possibility of attendance at foreign universities represented great importance. Nowadays, we possess a database with more than 100.000 records about Hungarian students who attended foreign universities before 1918. Many source editions, analyses and monographs were published in this topic. The purpose of the following article is to summarize the most notable volumes. Photo: pexels.com